Study of the association of serum procalcitonin with leukocytosis in predicting complicated acute appendicitis - Patel, Thana Ram; Jain, Amit; Agarwal, Lakshman; Choudhary, Vakta Ram; Bijarniya, Dinesh (International Surgery Journal, 2020)
Background: Delay in the diagnosis of complicated appendicitis and its treatment results in an increased rate of postoperative morbidity, mortality and hospital stay. The diagnosis of appendicitis rests on a combination of signs of inflammation such as fever, pain and tenderness; leukocytosis, and elevated C-reactive protein levels, interleukin-6 (IL6) and procalcitonin. Raised level of serum procalcitonin in bacterial infection has been used to further improve the diagnosis of complicated AA. Methods: One-hundred ten patients of appendicitis confirmed by intra-operative findings and final pathologist report, who underwent appendectomy consisting 25 women (22.73%) and 85 men (77.27%) with a mean age of 25 years (age range 15-55 years) were included in this study. Serum procalcitonin value was measured by chemi E411 Cobas method (chemilumiscent immunoassay system) using the B.R.A.H.M.S PCT kit. Serum PCT level >0.5 ng/ml was consider as risk for progression to severe systemic disease. Results: At a 0.5 ng/dl cut-off value of PCT, the sensitivity and specificity of PCT level measurement for acute complicated appendicitis prediction was 90% and 97.14% respectively. Association between WBC count and PCT value shows the sensitivity and specificity in 40 case of acute complicated appendicitis prediction was 86% and 75% respectively. Conclusions: Both the higher PCT values and leukocytosis correlates well with infectious post-operative complications for acute appendicitis and it can help to carry out timely surgical intervention which is highly recommended in complicated appendicitis(correlates PCT >0.5 ng/dl).